Strategi Social Media Marketing dan Marketplace Optimization untuk Meningkatkan Digital Consumer Trust pada UMKM Furniture - Rafly Anwar Alkaf; Amron Amron; Yohan Wismantoro; Roymon Panjaitan; Diana Aqmala; Ariati Anomsari (Jurnal Multidisiplin Indonesia, 2026)
The rapid growth of digital technology has encouraged furniture small and medium enterprises (SMEs) to strengthen their digital marketing strategies to enhance consumer trust. This study aims to analyze the role of social media marketing and marketplace optimization in improving digital consumer trust and their impact on online purchase decisions for furniture SMEs. A quantitative approach was employed using a survey of 240 consumers who had purchased furniture products through digital platforms. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that social media marketing and marketplace optimization have positive and significant effects on digital consumer trust. Furthermore, digital consumer trust positively influences online purchase decisions and mediates the relationship between both marketing strategies and purchase decisions. These results suggest that effective digital marketing strategies supported by optimized marketplace features can strengthen consumer trust and encourage online purchasing behavior. The study provides practical implications for furniture SMEs in designing integrated digital marketing strategies to improve competitiveness and business performance in the digital marketplace.